Impact of the COVID‐19 pandemic on medical student placements in rural Queensland: A survey study. (14th March 2022) - Martin, Priya; McGrail, Matthew; Fox, Jordan; Partanen, Riitta; Kondalsamy‐Chennakesavan, Srinivas
Abstract: Objective: The COVID‐19 pandemic has adversely impacted medical students' learning experiences. Students in one Australian Rural Clinical School were surveyed to investigate the impact of disruptions to clinical placements and satisfaction with educational changes implemented as a result of the pandemic. Design: Cross‐sectional survey. Setting: The University of Queensland Rural Clinical School. Methods: Students undertaking one or two years of study at the participating Rural Clinical School in November 2020. Main outcome measure: A 20‐item anonymised survey with questions on personal health and safety, quality of clinical training experience, response to changes in learning and student environment, and progression to completion of the medical degree. Results: The survey was completed by 124 students (76% response rate). Students were satisfied with the changes made to their learning to accommodate the disruptions to health service delivery and placements. Final year students were more satisfied with their learning experiences compared to their third‐year counterparts. Conclusions: The Rural Clinical School implemented a range of academic and psychological support strategies which appear to have helped with mitigating mental health concerns experienced by students completing rural placements, who are already prone to experiencing social isolation. Strengthening communication between the academic and health service sectors can improve the quality of learning for medical students on placements.